Heart Disease and Pectus Excavatum: An Underestimated Issue—Single Center Experience and Literature Review - Alice Ravasin; Domenico Viggiano; Simone Tombelli; Luca Checchi; Pierluigi Stefàno; Luca Voltolini; Alessandro Gonfiotti (Life)
Pectus excavatum (PE) can be associated with either congenital or acquired heart disease. This study highlights the importance of PE surgical repair in cases of severe chest depression on the heart in underlying cardiac diseases exacerbating cardiopulmonary impairment. From January 2023 to March 2024, four male patients underwent PE repair, having heart disease including pericarditis, mitral valve prolapse, ventricular fibrillation arrest and type 1 second-degree atrioventricular block. PE severity was determined by the Haller index (HI). Preoperative assessment included a pulmonary function test, chest computed tomography and cardiac evaluation. The Nuss procedure was performed in three patients, whereas, in one patient, it was performed in combination with a modified Ravitch procedure. The median HI was five. The median time of chest tube removal was 6.5 days. Postoperative complications were prolonged air leak, atrial fibrillation and atelectasis. The median length of hospital stay was 19.5 days, and no 30-day postoperative mortality was recorded. In all patients, surgical repair helped to resolve the underlying cardiological issues, and surgical follow-ups were deemed regular. PE is generally an isolated congenital chest wall abnormality, and, when associated with a heart disease, it can have severe life-threatening hemodynamic consequences due to mechanical compression on the heart for which surgical corrections should be considered.